A kind of carbon mineralized plate and preparation method thereof
By using industrial solid waste residue and other raw materials and regulators, carbon mineralized plates are prepared to solve the problem of land stacking and carbon dioxide emissions of silicon calcium solid waste, and achieve efficient solid waste utilization and low -carbon production.
Patent Information
- Application Number
- CN202411359809.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The problem of existing calcium silicon solid waste occupying and storage and the problem of high carbon dioxide emissions during the preparation process limit the profit and promotion prospects of the product.
The industrial solid waste residue, early strong agent, tough fiber and regulator (prepared by boron nitride, amino acid compounds and alkylchloride compounds) are used as raw materials, and carbon mineralized plates are prepared through spherical grinding, pulp and mineralized kettle.
It achieves high-value utilization of calcium silicate solid waste and reduces carbon dioxide emissions. The prepared carbon mineralized plates have high mechanical strength, low water absorption rate and high carbon fixation rate.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste cementitious material processing, and in particular to a carbon mineralized plate and a preparation method thereof. Background Art
[0002] With the rapid transformation of the industrial environmental development model, the traditional high-consumption, high-pollution model has begun to transform towards a green, low-carbon, and circular direction. Solid waste disposal is a key link in the transformation and development process. Compared with the previous land-occupying and stacking disposal method, the use of potentially active components such as calcium oxide and silicon oxide in industrial solid waste to prepare green and low-carbon materials has achieved high-value utilization of solid waste while solving environmental pressures.
[0003] Fiberboard made of silicon-calcium materials and reinforced fibers is a new type of building material. It has excellent fire resistance, moisture resistance and long service life, and is gradually becoming the protagonist of the environmentally friendly board market. However, due to the cost of raw materials and carbon emissions during the preparation process, its product profits and promotion prospects are limited. How to achieve large-scale storage of carbon dioxide is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings, one of the purposes of the present invention is to provide a carbon mineralization plate, which solves the problem of land-consuming storage of silicon-calcium solid waste and realizes the large-scale storage of carbon dioxide.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is: a carbon mineralized board, the raw materials for preparing which include, by weight: 15-60 parts of industrial solid waste residue, 1-12 parts of early strength agent, 1-15 parts of toughening fiber, and 1-5 parts of regulator.
[0006] Exemplarily, the industrial solid waste residue is in the range of 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts or any two of them; the early strength agent is in the range of 1 part, 3 parts, 5 parts, 7 parts, 10 parts, 12 parts or any two of them; the toughening fiber is in the range of 1 part, 3 parts, 5 parts, 7 parts, 10 parts, 12 parts, 15 parts or any two of them; the regulator is in the range of 1 part, 2 parts, 3 parts, 4 parts, 5 parts or any two of them.
[0007] Furthermore, the raw materials for preparation include, by weight: 20-55 parts of industrial solid waste residue, 3-10 parts of early strength agent, 3-12 parts of toughening fiber, and 1-4 parts of regulator.
[0008] Furthermore, the raw materials for preparing the regulator include 15-35 parts of boron nitride, 7-35 parts of amino acid compounds and 1-8 parts of alkyl acyl chloride compounds.
[0009] Furthermore, the amino acid compound is at least one of 3-aminopropionic acid, 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, and p-aminophenylbutyric acid.
[0010] Furthermore, the amino acid compound is at least one of 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, and p-aminophenylbutyric acid.
[0011] Furthermore, the alkyl chain length of the alkyl acid chloride compound is C5-C15.
[0012] Furthermore, the alkyl acyl chloride compound is at least one of octyl acyl chloride, nonyl acyl chloride, decyl acyl chloride, undecanoyl chloride and dodecanoyl chloride.
[0013] Furthermore, the mass ratio of boron nitride to the amino acid compound is 1:(0.1-2).
[0014] Exemplarily, the mass ratio of boron nitride to the amino acid compound is 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2 or a range consisting of any two of them.
[0015] Furthermore, the mass ratio of boron nitride to the amino acid compound is 1:(0.3-1).
[0016] Furthermore, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(3-8).
[0017] Illustratively, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or a range consisting of any two thereof.
[0018] Furthermore, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(4.5-5.5).
[0019] Furthermore, the preparation method of the regulator comprises the following steps:
[0020] (1) Boron nitride, an amino acid compound and water are mixed evenly, ball-milled, filtered, washed and dried to obtain modified boron nitride.
[0021] (2) Add ethanol and alkyl acyl chloride compound, ball mill, filter, wash and dry to obtain a regulator.
[0022] The ball milling medium is zirconium oxide grinding ball, and the mass ratio of the regulator preparation raw material to the ball milling medium is 1: (80-120).
[0023] The diameter of the zirconia grinding balls is 1-5 mm.
[0024] Furthermore, the preparation method of the regulator comprises the following steps:
[0025] (1) Boron nitride, amino acid compound and water are mixed evenly, ball milled at 1000-2000 rpm for 5-10 hours, filtered, washed and dried to obtain modified boron nitride.
[0026] (2) Add ethanol and alkyl acyl chloride compounds, ball mill for 1-3 hours, filter, wash with water, and dry to obtain a regulator.
[0027] The ball milling medium is zirconium oxide grinding ball, and the mass ratio of the regulator preparation raw material to the ball milling medium is 1: (90-110).
[0028] Furthermore, the industrial solid waste residue is at least one of silicon-calcium slag, commercial mixed waste slurry and construction fine powder.
[0029] Among them, commercial concrete waste slurry refers to the hardened slurry remaining around the equipment and pipelines during the concrete pumping process of commercial concrete mixing stations. After drying and grinding, its particle size is generally defined as less than 30 microns.
[0030] Construction micro powder refers to the micro powder generated by the demolition of old buildings, the construction of new buildings and the decoration of buildings, that is, the waste concrete, waste clay bricks and other construction waste are crushed and ground step by step to reach a certain fineness of fine powder, generally defined as a particle size less than 0.16mm.
[0031] Furthermore, the toughening fiber is at least one of pulp fiber, wood chip fiber and glass fiber.
[0032] Furthermore, the average particle size of the early strength agent is 0.8-2 μm.
[0033] Illustratively, the average particle size of the early strength agent is 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.7 μm, 2 μm, or a range consisting of any two thereof.
[0034] Furthermore, the raw materials for preparing the early strength agent include raw material A, raw material B and a grinding aid, and the mass ratio of raw material A to raw material B is (1-3):1.
[0035] Illustratively, the mass ratio of raw material A to raw material B is 1:1, 2:1, 3:1 or a range consisting of any two thereof.
[0036] Furthermore, the raw material A is at least one of fly ash, slag, magnesium slag and coal gangue.
[0037] Furthermore, raw material A is a mixture of fly ash and slag, and the mass ratio of fly ash to slag is (3-5):1.
[0038] Exemplarily, the mass ratio of fly ash to slag is 3:1, 4:1, 5:1 or a range consisting of any two thereof.
[0039] Further, the raw material B is at least one of carbide slag, red mud, steel slag and gypsum;
[0040] Furthermore, raw material B is at least one of carbide slag and red mud.
[0041] Furthermore, the grinding aid is at least one of triethanolamine, ethylene glycol and calcium formate.
[0042] Furthermore, the preparation method of the early strength agent comprises the following steps:
[0043] (1) Add raw material A to raw material B and mix evenly to obtain a mixed powder;
[0044] (2) Place the mixed powder into a ball mill, add a grinding aid, and perform ball milling to obtain an early strength agent.
[0045] In the ball mill, zirconia grinding balls with diameters of 8-11mm, 11-13mm, 13-15mm and 15-18mm are used as ball milling media; the ball milling media with a diameter of 8-11mm is recorded as m1, the ball milling media with a diameter of 11-13mm is recorded as m2, the ball milling media with a diameter of 13-15mm is recorded as m3, and the ball milling media with a diameter of 15-18mm is recorded as m4. By weight, the gradation relationship of the ball milling media is: m1:m2:m3:m4=(1-2):1:(1-2):1.
[0046] Furthermore, the ball milling speed in step (2) is 500-900 rpm.
[0047] Furthermore, in step (2), the mass ratio of the raw material for preparing the early strength agent to the grinding medium is 1:(7-13).
[0048] Furthermore, the conditioning agent and the early strength agent are prepared by an interlocking process, comprising the following steps:
[0049] (1) First, raw material B and water are mixed, and then boron nitride is added and ball milled to obtain a mixed material;
[0050] (2) adding an amino acid compound to the mixture of step (1), ball milling, filtering, and drying, and then adding ethanol and an alkyl acyl chloride compound, ball milling, filtering, and drying to obtain a mixture;
[0051] (3) Adding raw material A and a grinding aid to the mixture of step (2), and ball milling to obtain the mixture.
[0052] A second object of the present invention is to provide a method for preparing a carbon mineralized plate, comprising the following steps:
[0053] S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder;
[0054] S2, mixing the toughened fibers and water, and beating the mixture to obtain fiber slurry;
[0055] S3, fully mixing and beating the carbon-fixing powder and the fiber slurry to obtain a carbon-fixing slurry;
[0056] S4, the carbon-fixing slurry is slurried by a slurry flow machine, pressed and cut to obtain a fiberboard blank;
[0057] S5, placing the fiber slab into a pre-curing kiln for pre-curing, reducing the moisture content of the slab and accelerating hardening and demoulding;
[0058] S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce industrial flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
[0059] Furthermore, step S2 is specifically as follows: the toughened fiber and water are mixed in a mass ratio of 1:(7-11), the fixed speed of the refiner rotor is adjusted to 1200-1500rpm, the fixed speed of the pulp tank is adjusted to 500-700rpm, and the number of rotor revolutions is set to 20000-30000.
[0060] The fiber fibrillation rate after wet grinding by the pulping machine is relatively high, which can not only be more dispersed in the pulp and improve the mechanical properties of the product, but also provide more active sites for the later hydration products, optimize the internal pore structure, and improve the carbon fixation rate of the product.
[0061] For glass fiber, the mechanical friction of the pulping machine is used to break the glass fiber, causing fine filaments to form on its surface, thereby increasing its contact area with other components in the system and improving the mechanical strength and bonding properties of the product.
[0062] Furthermore, in step S3, the beating time is 10-20 minutes, the solid content of the toughening fiber in the solid carbon slurry is 6-8%, and the water content is 45-50%.
[0063] Furthermore, in step S4, the pressing plate process parameters are set to stress control, the pressure value is 15-25 MPa, and the holding time is 300-400 s.
[0064] Furthermore, in step S5, the pre-curing parameters are set as: temperature 60-80°C, humidity 95%, and time 4-6 hours.
[0065] Furthermore, in step S6, the mineralization parameters of the mineralization kettle are: mineralization pressure value 0.2~0.5MPa, mineralization temperature 50~80℃, mineralization reaction time 4~8h, and CO2 concentration in the introduced industrial flue gas is not less than 20%.
[0066] The beneficial effects of the present invention are:
[0067] 1) The present invention uses industrial solid waste residue, early strength agent, toughening fiber and regulator as raw materials to prepare a carbon mineralized plate with high mechanical strength, low water absorption and high carbon fixation rate.
[0068] 2) The present invention uses industrial solid waste residue as raw material, which solves the problem of land-occupying storage of silico-calcium solid waste. Compared with the use as auxiliary cementitious material admixture, the present invention combines the carbon fixation demand to carry out large-scale batch disposal of silico-calcium solid waste residue, and the prepared carbon mineralized board has a high carbon fixation rate, realizing the high-value utilization of industrial solid waste.
[0069] 3) A regulator was prepared using boron nitride, amino acid compounds, and alkyl acyl chloride compounds as raw materials. On the one hand, it improved the product's anti-permeability properties, and on the other hand, it was able to adjust the internal pore structure of the green body, increase the negative carbon degree, and optimize the product's mechanical strength.
[0070] 4) In the preparation process of the early strength agent of the present invention, the requirements for the raw materials of silico-calcium solid waste slag are not high. The early strength agent is prepared by the mechanical activation effect of the grinding process. The alkaline environment provided by the addition of alkaline solid waste during the grinding process is used to promote the hydration reaction process in the subsequent fiberboard pre-curing stage. The mechanical activation process reduces the surface potential energy of calcium salts and silicates inside the silico-calcium material, the silicon-oxygen ion bonds in the internal components are easier to break, and the particle size of the raw materials is reduced to the nano-micron level. On the one hand, it can increase its reaction specific surface area and improve the degree of subsequent mineralization reaction; on the other hand, nano-micron solid waste particles can act as crystal nuclei to provide nucleation sites, promote early reaction processes, provide early strength to the matrix, and help with flipping and demolding during the slab stacking process.
[0071] 5) The present invention regulates the moisture content and pore structure inside the slab, which is beneficial to the subsequent transmission and diffusion of CO2 inside the slab. Water, as a reaction medium for the mineralization reaction, promotes the gas-liquid-solid reaction. At the same time, the pore structure inside the brick is regulated by the pressing parameters of the press, which greatly promotes the dissolution of CO2 and the migration of ions. DETAILED DESCRIPTION
[0072] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0073] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0074] One embodiment of the present invention provides a carbon mineralized plate, wherein the raw materials for preparing the plate include, by weight:
[0075] Industrial solid waste
[0076] In some embodiments, 15-60 parts of industrial solid waste residue, preferably 20-55 parts;
[0077] In some embodiments, the industrial solid waste residue is at least one of silica-calcium slag, commercial mixed waste slurry and construction fine powder.
[0078] Early strength agent
[0079] In some embodiments, the early strength agent is 1-12 parts, preferably 3-10 parts.
[0080] In some embodiments, the average particle size of the early strength agent is 0.8-2 μm.
[0081] In some embodiments, the raw materials for preparing the early strength agent include raw material A, raw material B and a grinding aid, and the mass ratio of raw material A to raw material B is (1-3):1.
[0082] In some embodiments, raw material A is at least one of fly ash, slag, magnesium slag, and coal gangue.
[0083] In some embodiments, raw material A is a mixture of fly ash and slag, and the mass ratio of fly ash to slag is (3-5):1.
[0084] In some embodiments, raw material B is at least one of carbide slag, red mud, steel slag, and gypsum.
[0085] In some embodiments, raw material B is at least one of carbide slag and red mud.
[0086] In some embodiments, the grinding aid is at least one of triethanolamine, ethylene glycol, and calcium formate.
[0087] In some embodiments, the preparation method of the early strength agent comprises the following steps:
[0088] (1) Add raw material A to raw material B and mix evenly to obtain a mixed powder;
[0089] (2) Put the mixed powder into a ball mill, add a grinding aid, and ball mill at a ball milling speed of 500-900 rpm to obtain an early strength agent;
[0090] In step (2), in the ball mill, zirconium oxide grinding balls with diameters of 8-11 mm (m1), 11-13 mm (m2), 13-15 mm (m3) and 15-18 mm (m4) are used as ball milling media; by weight, the gradation relationship of the ball milling media is: m1: m2: m3: m4 = (1-2): 1: (1-2): 1. The mass ratio of the early strength agent preparation raw material to the ball milling media is 1: (7-13).
[0091] Conditioner
[0092] In some embodiments, the modifier is 1-5 parts, preferably 1-4 parts.
[0093] In some embodiments, the raw materials for preparing the regulator include 15-35 parts of boron nitride, 7-35 parts of amino acid compounds and 1-8 parts of alkyl acyl chloride compounds.
[0094] Boron nitride has a two-dimensional layer structure similar to graphene, with high specific surface area, low thermal expansion, good chemical stability and excellent mechanical properties, which can improve the mechanical properties of concrete. Boron nitride, amino acid compounds and alkyl acyl chloride compounds are used as raw materials to prepare a regulator, which, on the one hand, improves the product's impermeability, and on the other hand, can adjust the internal pore structure of the green body, increase the negative carbon level, and optimize the product's mechanical strength.
[0095] In some embodiments, the mass ratio of boron nitride to amino acid compound is 1:(0.1-2).
[0096] In some embodiments, the mass ratio of boron nitride to the amino acid compound is 1:(0.3-1).
[0097] In some embodiments, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(3-8). In some embodiments, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(4.5-5.5).
[0098] In some embodiments, the amino acid compound is at least one of 3-aminopropionic acid, 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminohexanoic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, and p-aminophenylbutyric acid;
[0099] In some embodiments, the amino acid compound is at least one of 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminohexanoic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, and p-aminophenylbutyric acid.
[0100] In some embodiments, the alkyl chain length of the alkyl acyl chloride compound is C5-C15;
[0101] In some embodiments, the alkyl acyl chloride compound is at least one of octyl acyl chloride, nonyl acyl chloride, decyl acyl chloride, undecanoyl chloride, and dodecanoyl chloride.
[0102] In some embodiments, the preparation method of the modulator comprises the following steps:
[0103] (1) Take boron nitride, amino acid compound and water, mix them evenly, ball mill them at 1000-2000 rpm for 5-10 hours, filter, wash and dry to obtain modified boron nitride.
[0104] (2) adding ethanol and alkyl acyl chloride compound, ball milling for 1-3 hours at the same ball milling speed, filtering, washing and drying to obtain a regulator;
[0105] In some embodiments, the ball milling medium is a zirconium oxide grinding ball, and the mass ratio of the conditioning agent preparation raw material to the ball milling medium is 1: (80-120), preferably 1: (90-110);
[0106] In some embodiments, the diameter of the zirconium oxide grinding balls is 1-5 mm, preferably 2-4 mm.
[0107] The amino acid compound enters the interlayer of the boron nitride, exfoliates it, and grafts amino active groups on its surface, thus obtaining modified boron nitride; the modified boron nitride is more evenly dispersed in the slurry system and has higher activity. The regulator is obtained by combining with an alkyl acyl chloride compound; the long alkyl chain of the alkyl acyl chloride compound adjusts the hydrophilicity of the modified boron nitride, allowing it to be evenly dispersed in the system, thereby improving the product's impermeability. In the alkaline environment of the slurry, the regulator provides more attachment points for the hydration product, thereby adjusting the growth orientation of the hydration product in the slurry and optimizing the pore structure inside the green body, so that more carbon dioxide can be adsorbed during the later carbon mineralization process, thereby improving the product's mechanical properties.
[0108] fiber
[0109] In some embodiments, the toughening fiber is 1-15 parts, preferably 3-12 parts.
[0110] In some embodiments, the toughening fibers are at least one of pulp fibers, wood chip fibers, and glass fibers.
[0111] The present invention also provides a method for preparing a carbon mineralized plate, which specifically comprises the following steps:
[0112] S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder.
[0113] S2, mixing the toughened fiber and water, beating the mixture to obtain fiber slurry;
[0114] S3, fully mix the carbon-fixing powder and the fiber slurry, and beat them to obtain the carbon-fixing slurry; the beating time is 10-20 minutes, and the solid content of the toughening fiber in the carbon-fixing slurry is 6-8%, and the water content is 45-50%;
[0115] S4, the carbon-fixing slurry is slurried by a slurry flow machine, and then subjected to a pressing and cutting process to obtain a fiberboard blank; the pressing process parameters are set to stress control, the pressure value is 15-25 MPa, and the holding time is 300-400 s.
[0116] S5. Put the fiber slab into a pre-curing kiln for pre-curing to reduce the moisture content of the slab and accelerate hardening and demoulding. The pre-curing parameters are set as follows: temperature 60-80°C, humidity 95%, and time 4-6 hours;
[0117] S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce industrial flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
[0118] Step S2 specifically comprises: mixing toughened fiber and water in a mass ratio of 1:(7-11), adjusting the fixed speed of the refiner rotor to 1200-1500rpm, the fixed speed of the pulp tank to 500-700rpm, and setting the rotor rotation number to 20000-30000.
[0119] The fiber fibrillation rate after wet grinding by the pulping machine is relatively high, which can not only be more dispersed in the pulp and improve the mechanical properties of the product, but also provide more active sites for the later hydration products, optimize the internal pore structure, and improve the carbon fixation rate of the product.
[0120] For glass fiber, the mechanical friction of the pulping machine is used to break the glass fiber, causing fine filaments to form on its surface, thereby increasing its contact area with other components in the system and improving the mechanical strength and bonding properties of the product.
[0121] The CO2 concentration in the industrial flue gas introduced shall not be less than 20%.
[0122] The mineralization parameters of the mineralization kettle are: mineralization pressure value 0.2~0.5MPa, mineralization temperature 50~80℃, and mineralization reaction time 4~8h.
[0123] In some embodiments, the regulator and the early strength agent can also be prepared by an interlocking process, including the following steps:
[0124] (1) Take each substance in equal proportion to the content in the fiberboard, first mix raw material B and water, then add boron nitride, and ball mill to obtain a mixed material;
[0125] (2) adding an amino acid compound to the mixture of step (1), ball milling, filtering, and drying, and then adding ethanol and an alkyl acyl chloride compound, ball milling, filtering, and drying to obtain a mixture;
[0126] (3) Adding raw material A and a grinding aid to the mixture of step (2), and ball milling to obtain the mixture.
[0127] The material obtained through the above steps contains both the regulator and the early strength agent.
[0128] Example
[0129] The following examples describe the disclosure of the present invention in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0130] Example 1
[0131] The raw materials for preparing a carbon mineralized plate include: 35.7 parts of industrial solid waste slag, 6.2 parts of early strength agent, 6.5 parts of toughening fiber, and 2.6 parts of regulator.
[0132] The raw materials for preparing the regulator include 25 parts of boron nitride, 17.5 parts of amino acid compound (4-aminobutyric acid) and 3.5 parts of alkyl acyl chloride compound (decyl acyl chloride). The parts of boron nitride, amino acid compound and alkyl acyl chloride compound are only used to clearly express the proportion of each component in the regulator, and have no corresponding relationship with the parts of the raw material regulator for preparing the carbon mineralization board.
[0133] The mass ratio of boron nitride to the amino acid compound is 25:17.5=1:0.7, and the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 3.5:17.5=1:5.
[0134] The raw materials for the preparation of the early strength agent include raw material A, raw material B and grinding aids, wherein raw material A includes 19 parts of fly ash and 5.5 parts of slag, raw material B (carbide slag) is 10.5 parts, and grinding aids (triethanolamine) are 2 parts. The proportions of raw material A (fly ash, slag), raw material B (carbide slag) and grinding aid (triethanolamine) are only for clearly expressing the proportional relationship between the components in the early strength agent, and have no corresponding relationship with the proportions of the raw material early strength agent for preparing carbon mineralized plates.
[0135] In raw material A, the mass ratio of fly ash to slag is 19:5.5=3.5:1.
[0136] The method for preparing the carbon mineralized plate comprises the following steps:
[0137] The present invention also provides a method for preparing a carbon mineralized plate, which specifically comprises the following steps:
[0138] S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder.
[0139] The preparation method of the early strength agent is:
[0140] (1) Add raw material A to raw material B and mix evenly to obtain a mixed powder;
[0141] (2) Place the mixed powder into a ball mill, add a grinding aid, and ball mill for 25 minutes at a ball milling speed of 750 rpm to obtain an early strength agent with a particle size of 1.5 μm.
[0142] In the ball mill, zirconium oxide with diameters of 10mm (m1), 12mm (m2), 14mm (m3) and 16mm (m4) is used as ball milling media; the mass ratio of material to grinding media is 1:10, and the grading relationship of the ball milling media is: m1:m2:m3:m4=1.5:1:1.5:1 (weight ratio).
[0143] The preparation method of the regulator comprises the following steps:
[0144] (1) Boron nitride, amino acid compound and water are mixed evenly, ball milled at 1500 rpm for 8 h, filtered, washed and dried to obtain modified boron nitride;
[0145] (2) adding ethanol and alkyl acyl chloride compound, ball milling for 2 hours at a ball milling speed of 1500 rpm, filtering, washing and drying to obtain a regulator;
[0146] The ball milling medium is a zirconium oxide grinding ball, and the diameter of the zirconium oxide grinding ball is 3 mm. The mass ratio of the raw material for preparing the regulator to the ball milling medium is 1:100. The amount of water in step (1) and the amount of ethanol in step (2) can be used for smooth wet grinding, and there is no specific limit on the amount.
[0147] S2. Mix pulp fiber and water in a mass ratio of 1:9, adjust the fixed speed of the refiner rotor to 1300 rpm, the fixed speed of the pulp tank to 600 rpm, set the number of rotor revolutions to 25000, and obtain fiber pulp.
[0148] S3. Fully mix the carbon-fixing powder and fiber pulp, and beat for 15 minutes to obtain the carbon-fixing pulp. The solid content of pulp fiber in the carbon-fixing pulp is 6.84%, and the water content is 46.3%.
[0149] S4, the carbon-fixing slurry is slurried by a slurry flow machine, and then subjected to a pressing and cutting process to obtain a fiberboard blank; the pressing process parameters are set to stress control, the pressure value is 20 MPa, and the holding time is 350 s.
[0150] S5. Place the fiber slab into a pre-curing kiln for pre-curing to reduce the moisture content of the slab and accelerate hardening and demoulding. The pre-curing parameters are set as follows: time 5h, temperature 70°C, and humidity 95%.
[0151] S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce coal chemical flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
[0152] The CO2 concentration in the flue gas introduced into the coal chemical industry is 75%.
[0153] The mineralization parameters of the mineralization kettle are: mineralization pressure value 0.4MPa, mineralization temperature 65℃, and mineralization reaction time 6h.
[0154] Example 2
[0155] The raw materials for preparing a carbon mineralized plate include: 20 parts of industrial solid waste residue, 3.5 parts of early strength agent, 3.3 parts of toughening fiber and 1.5 parts of regulator.
[0156] The raw materials for preparing the regulator include 15 parts of boron nitride, 7.5 parts of amino acid compound (4-aminobutyric acid) and 1.4 parts of alkyl acyl chloride compound (decyl acyl chloride). The parts of boron nitride, amino acid compound and alkyl acyl chloride compound are only used to clearly express the proportion of each component in the regulator, and have no corresponding relationship with the parts of the raw material regulator for preparing the carbon mineralization board.
[0157] The mass ratio of boron nitride to the amino acid compound is 15:7.5=1:0.5, and the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1.4:7.5=1:5.36.
[0158] The raw materials for the preparation of the early strength agent include raw material A, raw material B and grinding aids, wherein raw material A includes 9 parts of fly ash and 2.7 parts of slag, raw material B (carbide slag) is 5 parts, and grinding aid (triethanolamine) is 1 part. The parts of raw material A (fly ash, slag), raw material B (carbide slag) and grinding aid (triethanolamine) are only for clearly expressing the proportional relationship between the components in the early strength agent, and have no corresponding relationship with the parts of the raw material early strength agent for preparing carbon mineralized plates.
[0159] In raw material A, the mass ratio of fly ash to slag is 9:2.7=3.3:1.
[0160] A method for preparing a carbon mineralized plate comprises the following steps:
[0161] The present invention also provides a method for preparing a carbon mineralized plate, which specifically comprises the following steps:
[0162] S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder.
[0163] The preparation method of the early strength agent is as follows:
[0164] (1) Add raw material A to raw material B and mix evenly to obtain a mixed powder;
[0165] (2) Put the mixed powder into a ball mill, add a grinding aid, and ball mill for 20 minutes at a ball milling speed of 600 rpm to obtain an early strength agent with a particle size of 1 μm;
[0166] In the ball mill, zirconium oxide with diameters of 9mm (m1), 11mm (m2), 13mm (m3) and 15mm (m4) is used as the ball milling medium; by weight, the mass ratio of material to grinding medium is 1:8, and the grading relationship of the ball milling medium is: m1:m2:m3:m4=1:1:1:1 (weight ratio).
[0167] The preparation method of the regulator comprises the following steps:
[0168] (1) Boron nitride, amino acid compound and water are mixed evenly, ball milled at 1000 rpm for 10 h, filtered, washed and dried to obtain modified boron nitride;
[0169] (2) adding ethanol and acyl chloride compound, ball milling for 3 hours at a ball milling speed of 1000 rpm, filtering, washing and drying to obtain a regulator;
[0170] The ball milling medium is zirconium oxide grinding ball, and the mass ratio of the regulator preparation raw material to the ball milling medium is 1:90.
[0171] The diameter of the zirconium oxide grinding ball is 4 mm. The amount of water in step (1) and the amount of ethanol in step (2) are sufficient for smooth wet grinding, and there is no specific limitation on the amount.
[0172] S2. Mix pulp fiber and water in a mass ratio of 1:7, adjust the fixed speed of the refiner rotor to 1200 rpm, the fixed speed of the pulp tank to 500 rpm, and set the number of rotor revolutions to 20,000.
[0173] S3. Fully mix the carbon-fixing powder and fiber pulp, and beat for 10 minutes to obtain the carbon-fixing pulp. The solid content of pulp fiber in the carbon-fixing pulp is 6.19%, and the water content is 46.9%.
[0174] S4, the carbon-fixing slurry is slurried by a slurry flow machine, and then subjected to a pressing and cutting process to obtain a fiberboard blank; the pressing process parameters are set to stress control, the pressure value is 15 MPa, and the holding time is 400 s.
[0175] S5. Put the fiber slab into a pre-curing kiln for pre-curing to reduce the moisture content of the slab and accelerate hardening and demoulding. The pre-curing parameters are set as follows: time 4h, temperature 80°C, humidity 95%;
[0176] S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce coal chemical flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
[0177] The CO2 concentration in the flue gas introduced into the coal chemical industry is 70%.
[0178] The mineralization parameters of the mineralization kettle are: mineralization pressure value 0.2MPa, mineralization temperature 50℃, and mineralization reaction time 8h.
[0179] Example 3
[0180] The raw materials for preparing a carbon mineralized plate include: 55 parts of industrial solid waste slag, 9.5 parts of early strength agent, 11.5 parts of toughening fiber and 4 parts of regulator.
[0181] The raw materials for preparing the regulator include 35 parts of boron nitride, 35 parts of amino acid compound (4-aminobutyric acid) and 7.7 parts of alkyl acyl chloride compound (decyl acyl chloride). The parts of boron nitride, amino acid compound and alkyl acyl chloride compound are only used to clearly express the proportion of each component in the regulator, and have no corresponding relationship with the parts of the raw material regulator for preparing the carbon mineralization board.
[0182] The mass ratio of boron nitride to the amino acid compound is 35:35=1:1, and the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 7.7:35=1:4.5.
[0183] The raw materials for the preparation of the early strength agent include raw material A, raw material B and grinding aids, wherein raw material A includes 27 parts of fly ash and 8 parts of slag, raw material B (carbide slag) is 15 parts, and grinding aids (triethanolamine) are 3 parts. The proportions of raw material A (fly ash, slag), raw material B (carbide slag) and grinding aid (triethanolamine) are only for clearly expressing the proportional relationship between the components in the early strength agent, and have no corresponding relationship with the proportions of the raw material early strength agent for preparing carbon mineralized plates.
[0184] In raw material A, the mass ratio of fly ash to slag is 27:8=3.4:1.
[0185] A method for preparing a carbon mineralized plate comprises the following steps:
[0186] The present invention also provides a method for preparing a carbon mineralized plate, which specifically comprises the following steps:
[0187] S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder.
[0188] The preparation method of the early strength agent is as follows:
[0189] (1) Add raw material A to raw material B and mix well to obtain a mixed powder.
[0190] (2) The mixed powder was placed in a ball mill, and a grinding aid was added. The ball mill was milled for 30 minutes at a speed of 900 rpm to obtain an early strength agent with a particle size of 1.8 μm.
[0191] In the ball mill, zirconium oxide with diameters of 11mm (m1), 13mm (m2), 15mm (m3) and 18mm (m4) is used as the ball milling medium; by weight, the mass ratio of material to grinding medium is 1:13, and the grading relationship of the ball milling medium is: m1:m2:m3:m4=2:1:2:1 (weight ratio).
[0192] The preparation method of the regulator comprises the following steps:
[0193] (1) Boron nitride, amino acid compound and water are mixed evenly, ball milled at 2000 rpm for 5 h, filtered, washed and dried to obtain modified boron nitride.
[0194] (2) Add ethanol and acyl chloride compound, ball mill for 1 h at a ball milling speed of 2000 rpm, filter, wash and dry to obtain a regulator.
[0195] The ball milling medium is zirconium oxide grinding balls, and the mass ratio of the regulator preparation raw material to the ball milling medium is 1:110.
[0196] The diameter of the zirconium oxide grinding ball is 2 mm. The amount of water in step (1) and the amount of ethanol in step (2) is sufficient for smooth wet grinding, and there is no specific limitation on the amount.
[0197] S2. Mix pulp fiber and water in a mass ratio of 1:11, adjust the fixed speed of the refiner rotor to 1500 rpm, the fixed speed of the pulp tank to 700 rpm, and set the number of rotor revolutions to 30,000.
[0198] S3, fully mix the carbon-fixing powder and the fiber pulp, and beat for 20 minutes to obtain the carbon-fixing pulp, in which the solid content of the pulp fiber is 7.88% and the water content is 45.21%.
[0199] S4, the carbon-fixing slurry is slurried by a slurry flow machine, and then subjected to a pressing and cutting process to obtain a fiberboard blank; the pressing process parameters are set to stress control, the pressure value is 25 MPa, and the holding time is 300 s.
[0200] S5. Put the fiber slab into a pre-curing kiln for pre-curing to reduce the moisture content of the slab and accelerate hardening and demoulding. The pre-curing parameters are set as: time 6h, temperature 60°C, and humidity 95%.
[0201] S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce coal chemical flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
[0202] The CO2 concentration in the flue gas introduced into the coal chemical industry is 80%.
[0203] The mineralization parameters of the mineralization kettle are: mineralization pressure value 0.5MPa, mineralization temperature 80℃, and mineralization reaction time 4h.
[0204] Example 4
[0205] Example 4 is basically the same as Example 1, the main difference being that the raw materials boron nitride and amino acid compound used to prepare the regulator are used in different amounts, specifically 35 parts of boron nitride and 7.5 parts of amino acid compound (4-aminobutyric acid), and the mass ratio of boron nitride to amino acid compound is 35:7.5=1:0.2.
[0206] Example 5
[0207] Example 5 is basically the same as Example 1, the main difference being that the raw materials boron nitride and amino acid compound used to prepare the regulator are used in different proportions, specifically 17.5 parts of boron nitride and 25 parts of amino acid compound (4-aminobutyric acid), and the mass ratio of boron nitride to amino acid compound is 17.5:25=1:1.4.
[0208] Example 6
[0209] Example 6 is basically the same as Example 1, the main difference being that the raw material amino acid compound and alkyl acyl chloride compound used to prepare the regulator have different proportions, specifically, the amino acid compound (4-aminobutyric acid) is 18.4 parts, the alkyl acyl chloride compound (decyl chloride) is 2.6 parts, and the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 2.6:18.4=1:7.1.
[0210] Example 7
[0211] Example 7 is basically the same as Example 1, the main difference being that the raw material amino acid compound and alkyl acyl chloride compound used to prepare the regulator have different proportions, specifically, the amino acid compound (4-aminobutyric acid) is 15.8 parts, the alkyl acyl chloride compound (decyl chloride) is 5.2 parts, and the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 5.2:15.8=1:3.
[0212] Example 8
[0213] Example 8 is substantially the same as Example 1, with the main difference being that the amino acid compound used in Example 8 is specifically p-aminophenylbutyric acid.
[0214] Example 9
[0215] Example 9 is substantially the same as Example 1, with the main difference being that the amino acid compound used in Example 9 is specifically 11-aminoundecanoic acid.
[0216] Example 10
[0217] Example 10 is basically the same as Example 1, the main difference being that the conditioning agent and the early strength agent are prepared by an interlocking process, specifically comprising the following steps:
[0218] (1) Take each material in equal proportion to the content in the fiberboard of Example 1, first mix raw material B (carbide slag) and water, then add boron nitride, and ball mill at 1500 rpm for 1 hour to obtain a mixed material;
[0219] (2) adding an amino acid compound to the mixture of step (1), ball milling at 1500 rpm for 7 h, filtering and drying, and then adding ethanol and an alkyl acyl chloride compound to the dried product, ball milling at 1500 rpm for 2 h, filtering and drying to obtain a mixture;
[0220] (3) Add raw material A and a grinding aid to the mixture of step (2), and ball mill at 750 rpm for 25 min to obtain the product.
[0221] The amount of water in step (1) and the amount of ethanol in step (2) is not limited to any specific amount as long as it can smoothly wet grind.
[0222] Comparative Example 1
[0223] Comparative Example 1 is substantially the same as Example 1, the main difference being that the alkyl acyl chloride compound is butyl acyl chloride.
[0224] Comparative Example 2
[0225] Comparative Example 2 is substantially the same as Example 1, the main difference being that the raw materials for preparing the regulator are: 25 parts of boron nitride, 0 parts of an amino acid compound (4-aminobutyric acid), and 21 parts of an alkyl acyl chloride compound (decyl acyl chloride).
[0226] Comparative Example 3
[0227] Comparative Example 3 is substantially the same as Example 1, the main difference being that the raw materials for preparing the regulator are: 25 parts of boron nitride, 21 parts of an amino acid compound (4-aminobutyric acid), and 0 parts of an alkyl acyl chloride compound (4-aminobutyric acid).
[0228] Comparative Example 4
[0229] Comparative Example 3 is substantially the same as Example 1, the main difference being that the raw materials for preparing the regulator are: 25 parts of boron nitride, 0 parts of an amino acid compound (4-aminobutyric acid), and 0 parts of an alkyl acyl chloride compound (4-aminobutyric acid).
[0230] Experimental Examples
[0231] The saturated flexural strength, water absorption rate, water absorption rate and carbon fixation rate of the carbon mineralized plates prepared in Examples 1-10 and Comparative Examples 1-4 were tested, and the test results are shown in Table 1. Among them:
[0232] With reference to JC / T2604-2021 "Stone-like concrete panels and tiles", the flexural strength test was carried out on the carbon mineralized panels obtained in Examples 1-10 and Comparative Examples 1-4.
[0233] With reference to GB / T4111-2013 “Test methods for concrete blocks and bricks”, the water absorption rate of the carbon mineralized plates obtained in Examples 1-10 and Comparative Examples 1-4 was tested.
[0234] Table 1:
[0235]
[0236] In Examples 1 to 3, by limiting the type and amount of raw materials and adjusting the preparation process, the prepared carbon mineralized plates have high mechanical strength, low water absorption, and high carbon fixation rate. The saturated flexural strength reaches above 18.25 MPa, the water absorption is below 6.96%, and the carbon fixation rate reaches above 10.88%.
[0237] Compared with Example 1, Example 4 shows a decrease in various properties of the fiberboard, which may be due to: a small amount of amino acid compound is used, the exfoliation of boron nitride is insufficient, the activity of boron nitride is weakened, and its dispersion in the system is reduced, failing to provide sufficient, evenly dispersed attachment points for hydration products; moreover, a reduced amount of amino acid layer insertion will lead to a decrease in the amount of grafted alkyl acyl chloride compounds, a decrease in the hydrophobic effect of the long-chain alkyl group, and a decrease in the impermeability; in addition, the optimization effect of the regulator on the internal pore structure of the blank is reduced, and the internal pores of the blank are disordered, which is not conducive to the improvement of the mechanical strength and impermeability of the fiberboard, and its adsorption of carbon dioxide.
[0238] Compared with Example 1, the performance of the fiberboard in Example 5 is reduced. The reason may be that although the content of amino acid compound increases, it helps to improve the degree of exfoliation of boron nitride, but the amount of boron nitride is significantly reduced, so the mechanical properties and impermeability of the product are reduced; at the same time, from the data, the carbon fixation rate is also reduced. Therefore, the mass ratio of boron nitride to amino acid compound is 1: (0.1-2), preferably 1: (0.3-1).
[0239] Compared with Example 1, the decrease in the impermeability of the fiberboard in Example 6 may be due to the reduction of the alkyl acyl chloride compound, which reduces the hydrophobicity of the regulator.
[0240] Compared with Example 1, the reason for the decrease in various properties in Example 7 may be that the amount of the amino acid compound is relatively reduced, resulting in poor exfoliation effect of boron nitride, reduced porosity, low carbon fixation rate, and fewer attachment points of the hydration product brought by the regulator and uneven dispersion, so the mechanical strength of the product is poor. Therefore, the mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1: (3-8), preferably 1: (4.5-5.5).
[0241] The reason why the fiberboard has excellent properties compared with Example 1 may be that the benzene ring in the structure of p-aminobenzoic acid can not only provide a certain strength, but also the presence of the benzene ring is more conducive to the exfoliation of boron nitride and the stability of the pores, and can make the modified boron nitride more dispersed. The regulator can provide more dispersed and uniform attachment points for the hydration product, which is conducive to filling the gaps and optimizing the pore channels inside the blank. Therefore, the product has excellent mechanical strength, impermeability and carbon fixation rate.
[0242] Compared with Example 1, Example 9 has excellent performance in various properties of the fiberboard. The relatively shorter carbon chain in Example 1 can also achieve better results. It can be selected as needed in actual situations.
[0243] Compared with Example 1, the reason why the strength of Example 10 is significantly improved may be that after the carbide slag contacts water, an alkaline environment is provided for the regulator, which helps to weaken the interlayer force of boron nitride, and helps the modification of boron nitride by amino acid compounds, and the active sites of the modified boron nitride are more. The regulator generated with the alkyl acyl chloride compound has good dispersibility and can better regulate the internal pore structure of the blank, so the various properties of the product are all better. However, compared with Example 1, its process is relatively complicated.
[0244] Compared with Example 1, the reason why the impermeability of the fiberboard decreases in Comparative Example 1 may be that the hydrophobic alkyl chain of the alkyl acyl chloride compound (butyl acyl chloride) is shorter and the hydrophobicity of the regulator is poor, resulting in a decrease in the impermeability of the product. In addition, judging from the data, the mechanical properties and carbon fixation rate of the product also decrease.
[0245] Compared with Example 1, the reasons for the decline in various properties of the fiberboard in Comparative Example 2 may be that: no amino acid compound is used in the regulator, the degree of exfoliation of boron nitride is significantly reduced, and the number of attachment points provided for hydration products is significantly reduced, resulting in a poor pore structure inside the blank, so the mechanical properties, impermeability and carbon fixation rate of the product are significantly reduced.
[0246] Compared with Example 1, in Comparative Example 3, the amino acid compound can only play a stripping effect on boron nitride, and the anti-permeability performance is significantly deteriorated.
[0247] Compared with Example 1, Comparative Example 4 shows a significant decline in various properties of the fiberboard. The possible reason is that the dispersion uniformity of boron nitride in the system is poor, and the attachment points provided for the hydration product are also relatively few, which cannot effectively adjust the pore structure inside the blank, so the various properties of the product are declined.
[0248] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, change of structural morphology, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0249] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0250] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0251] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0252] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A carbon mineralized plate, characterized in that: The raw materials for preparation include, by weight: 15-60 parts of industrial solid waste residue, 1-12 parts of early strength agent, 1-15 parts of toughening fiber, and 1-5 parts of regulator; The raw materials for preparing the regulator include boron nitride, an amino acid compound and an alkyl acyl chloride compound; The alkyl chain length of the alkyl acyl chloride compound is C5-C15; The mass ratio of the boron nitride to the amino acid compound is 1:(0.1-2); The mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(3-8); The amino acid compound is at least one of 3-aminopropionic acid, 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid and p-aminophenylbutyric acid; The raw materials for preparing the early strength agent include raw material A, raw material B and grinding aids. The raw material A is at least one of fly ash, slag, magnesium slag and coal gangue; The raw material B is at least one of carbide slag, red mud, steel slag and gypsum; The grinding aid is at least one of triethanolamine, ethylene glycol and calcium formate; The industrial solid waste residue is at least one of silicon-calcium slag, commercial mixed waste slurry and construction fine powder.
2. The carbon mineralized plate according to claim 1, characterized in that: In the raw materials for preparing the regulator, the mass ratio of the boron nitride to the amino acid compound is 1:(0.3-1); The mass ratio of the alkyl acyl chloride compound to the amino acid compound is 1:(4.5-5.5); The alkyl acyl chloride compound is at least one of octyl acyl chloride, nonyl acyl chloride, decyl acyl chloride, undecanoyl chloride and dodecanoyl chloride; The amino acid compound is at least one of 4-aminobutyric acid, 5-aminopentanoic acid, 6-aminocaproic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid and p-aminophenylbutyric acid.
3. The carbon mineralized plate according to claim 1, characterized in that: The toughening fiber is at least one of pulp fiber, wood chip fiber and glass fiber.
4. The carbon mineralized plate according to claim 1, characterized in that: The average particle size of the early strength agent is 0.8-2 μm; the mass ratio of raw material A to raw material B is (1-3):
1.
5. The carbon mineralized plate according to claim 4, characterized in that: The raw material A is a mixture of fly ash and slag, and the mass ratio of fly ash to slag is (3-5):1; The raw material B is at least one of carbide slag and red mud.
6. The carbon mineralized plate according to any one of claims 4 or 5, characterized in that: The preparation method of the early strength agent comprises the following steps: (1) Add raw material A to raw material B and mix evenly to obtain a mixed powder; (2) Put the mixed powder into a ball mill, add a grinding aid, and ball mill to obtain an early strength agent; In the ball mill, zirconia grinding balls with diameters of 8-11mm, 11-13mm, 13-15mm and 15-18mm are used as ball milling media; the ball milling media with a diameter of 8-11mm is recorded as m1, the ball milling media with a diameter of 11-13mm is recorded as m2, the ball milling media with a diameter of 13-15mm is recorded as m3, and the ball milling media with a diameter of 15-18mm is recorded as m4. By weight, the gradation relationship of the ball milling media is: m1:m2:m3:m4=(1-2):1:(1-2):
1.
7. The carbon mineralized plate according to claim 1, characterized in that: The preparation method of the regulator comprises the following steps: (1) mixing boron nitride, an amino acid compound and water uniformly, ball milling, filtering, washing and drying to obtain modified boron nitride; (2) adding ethanol and alkyl acyl chloride compound, ball milling, filtering, washing and drying to obtain a regulator; The ball milling medium is zirconium oxide grinding balls, and the mass ratio of the regulator preparation raw material to the ball milling medium is 1: (80-120); The diameter of the zirconium oxide grinding ball is 1-5 mm.
8. A method for preparing the carbon mineralized plate material according to any one of claims 1 to 7, characterized in that: The steps include: S1. Take industrial solid waste residue, early strength agent and regulator, mix them evenly to obtain carbon-fixing powder; S2, mixing the toughened fibers and water, and beating the mixture to obtain fiber slurry; S3, fully mixing and beating the carbon-fixing powder and the fiber slurry to obtain a carbon-fixing slurry; S4, the carbon-fixing slurry is slurried by a slurry flow machine, pressed and cut to obtain a fiberboard blank; S5, placing the fiber slab into a pre-curing kiln for pre-curing, reducing the moisture content of the slab and accelerating hardening and demoulding; S6. Put the pre-cured and demoulded slab into a mineralization kettle, seal the kettle body, introduce industrial flue gas, adjust the ventilation parameters of the mineralization kettle, and prepare a carbon mineralized plate.
9. The method for preparing the carbon mineralized plate according to claim 8, characterized in that: In step S3, the beating time is 10-20 minutes, the solid content of toughening fiber in the solid carbon slurry is 6-8%, and the water content is 45-50%; In step S4, the platen process parameters are set to stress control, the pressure value is 15-25 MPa, and the holding time is 300-400 s; In step S5, the pre-curing parameters are set as follows: temperature 60-80° C., humidity 95%, and time 4-6 hours; In step S6, the mineralization parameters of the mineralization kettle are: mineralization pressure value 0.2~0.5MPa, mineralization temperature 50~80℃, mineralization reaction time 4~8h, and CO2 concentration in the introduced industrial flue gas is not less than 20%.
Citation Information
Patent Citations
Foam concrete based on high-activity calcium-based carbon absorption and preparation method thereof
CN115784769A
Method for preparing carbon sequestration product from calcium-silicon-based solid waste under composite curing system
CN117024104A